"AKSI GERCEPS" training program to support nutritional knowledge of adolescent integrated health centre cadres in Sampang Regency - Nuraini Fauziah; Kristian Triatmaja Raharja; Nindi Pramesthi Vardila Putri; Nadia Dian Rosanti; Renidya Asyura Muttabi' Deya Fa'ni; Cucun Setya Ferdina; Honesty Pujiyani; Abdan Syakura; Ahmad Mustofa (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: After the covid-19 pandemic, adolescent Integrated Health Centre (IHC) activities in Sampang Regency decreased drastically, both in quantity and quality. Factors related to this problem are the lack of adolescent participation, accompanied by the lack of ability of adolescent IHC cadres to perform their duties. Adolescent IHC is preventive efforts to prevent incidents of stunting.Objective: The study aimed to measure the effect of "AKSI GERCEPS" training on nutrition knowledge among adolescent IHC cadres in Sampang Regency.Methods: : Study quasi-experimental use one-group pretest-posttest design. The research was conducted in Sampang Regency in December 2023. The sample consisted of 72 people, selected using a purposive sampling method representing 12 locus villages stunting. The research variable is the effect of "AKSI GERCEPS" training on increasing the nutritional knowledge of adolescent IHC cadres. Data analysis used the T-test.  Results: Mean scores before and after training were significantly different (p=0,000). At the end of the training, the participants' average score increased to 6,58, whereas before the training  was 2,55. The knowledge of adolescent cadres who had previously received nutrition education was also significantly different from that of those who had never received nutrition education (p=0,000). After the training, cadres who had received nutrition education had an average score of 1,78 higher.Conclusion: Cadres knowledge of nutrition increased after the training. Nutrition training for adolescents needs to be carried out continuously, to be able to provide optimal service.